2003
DOI: 10.1682/jrrd.2003.09.0381
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Pain Outcomes Questionnaire-VA

Abstract: Abstract-The development of effective pain treatment strategies requires the availability of precise and practical measures of treatment outcomes, the importance of which has been noted in the Veterans Health Administration's (VHA's) National Pain Initiative. This paper presents the results of a 5-year collaborative effort to develop and validate a comprehensive and efficient self-report measure of pain treatment outcomes. Two samples of veterans (957 total subjects) undergoing inpatient Key words: chronic pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 51 publications
1
85
0
Order By: Relevance
“…This is similar to Keogh et al's finding, where females returned to baseline levels of pain intensity versus males [20]. While both sexes had statistically significant decreases in pain intensity at discharge, the effect sizes for females were medium, indicating a clinically significant change [29], whereas the effect size for males was small, meaning females actually made greater gains while in the program but were unable to maintain them. At 3 mo, effect sizes were small across sexes; however, it is important to note that the treatment modality is a tertiary-level inpatient pain rehabilitation program in which the population served represents those individuals who have the most chronic and treatment-refractory conditions.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This is similar to Keogh et al's finding, where females returned to baseline levels of pain intensity versus males [20]. While both sexes had statistically significant decreases in pain intensity at discharge, the effect sizes for females were medium, indicating a clinically significant change [29], whereas the effect size for males was small, meaning females actually made greater gains while in the program but were unable to maintain them. At 3 mo, effect sizes were small across sexes; however, it is important to note that the treatment modality is a tertiary-level inpatient pain rehabilitation program in which the population served represents those individuals who have the most chronic and treatment-refractory conditions.…”
Section: Discussionsupporting
confidence: 86%
“…Pain treatment outcomes were assessed using the Pain Outcomes Questionnaire-VA (POQ-VA) [29], which is a multidomain pain assessment instrument developed and validated specifically for Veterans. The POQ-VA assesses treatment outcomes across the major pain-related domains of functioning identified by the Rehabilitation Accreditation Commission (2002) as essential for comprehensive outcome measurement [29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 For evaluation of pain, the Pain Outcomes Questionnaire (POQ-VA) was used. 9 It is a primary pain outcome tool comprising 19 items examining pain history, average pain intensity, pain interference, emotional distress, painrelated fear, satisfaction with treatment and medication use. The numerical rating scale ranges from 0 (no pain interference) to 10 (significant pain interference).…”
Section: Self Report Measuresmentioning
confidence: 99%
“…Results of these studies are often significant in terms of their implications for clinical practice and health policy, not only for the VHA, but also for the broader healthcare delivery system. Studies by Clark et al have reported on pain treatment outcome measures that were specifically developed and normed on veteran samples [11]. Several investigators have examined the role of psychological factors in the management of persistent pain among veteran samples [12][13][14].…”
Section: Peer-reviewed Publicationsmentioning
confidence: 99%